2015
DOI: 10.1371/journal.pone.0137898
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Calcifications on Breast Ultrasound Shear Wave Elastography: An Investigational Study

Abstract: PurposeTo investigate the effects of macrocalcifications and clustered microcalcifications associated with benign breast masses on shear wave elastography (SWE).MethodsSuperSonic Imagine (SSI) and comb-push ultrasound shear elastography (CUSE) were performed on three sets of phantoms to investigate how calcifications of different sizes and distributions influence measured elasticity. To demonstrate the effect in vivo, three female patients with benign breast masses associated with mammographically-identified c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 53 publications
3
14
1
Order By: Relevance
“…These results correlate with previous findings (31). Figure 7 shows an example of a false positive benign nodule by SWE containing macrocalcifications.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results correlate with previous findings (31). Figure 7 shows an example of a false positive benign nodule by SWE containing macrocalcifications.…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, from the 16 thyroid nodules identified as false positives cases, 9 (56.25%) nodules contained macrocalcifications and 2 (12.5%) nodules had microcalcifications. Thus, benign nodules with calcifications can be perceived as malignant nodules based on ultrasound SWE (31). Additional nodule features such as cystic component and nodule size did not have an effect on shear wave speed measurements among benign and malignant nodules; on the other hand, benign nodules in patients with goiter and benign nodules with a vascular component (identified by using color Doppler imaging) showed reduced elasticity compared to nodules inside normal size thyroid glands and avascular nodules, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Another issue comes from the effect of calcification: the surrounding zones are hardened, making the elasticity estimation higher. If the ROI selected matches this area, a misdiagnosis may be expected [193].…”
Section: Breastmentioning
confidence: 99%
“…This result may have been a consequence of the amount of microcalcification. It was suggested by Gregory et al that highly concentrated microcalcifications can influence stiffness more than low concentrations …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the presence of calcification may be another factor affecting stiffness in breast cancer. In a recent study, Gregory et al found that large isolated macrocalcifications and highly concentrated clusters of microcalcifications showed higher stiffness in benign breast masses …”
mentioning
confidence: 99%